Emotional Education in the Venezuelan University Curriculum. Present or absent? - Torres-López, Alexaivy del Valle (2022)
Introduction. For Maturana (2005), saying that reason defines what is human is like putting blinders on because it leaves us blind to emotion, which is devalued as something animal, or as something that denies the rational. However, science speaks today of the role of emotions and their neurological processes as important elements in the behavior and learning of the individual. Purpose. The present essay, as a product of the dissertations achieved in the doctoral thesis, aims to present to the community the role of emotional education in the university curricula for teacher training in Venezuela, approached from the interpretive paradigm and hermeneutic phenomenology. Discussion. From the experience and the expressions of some key informants, interviewed in the doctoral research and used in this essay, some primordial key aspects are established, which could be fundamental, nowadays, in the conception or genesis of a curriculum that excludes emotions from the training of Venezuelan teachers. Conclusion. The inclusion of emotional education in the university curriculum is becoming increasingly necessary, and this criterion coincides with the premises of Goleman, Bisquerra, Morin, Freire, and other theorists who have delved into the subject. However, when we analyze the curriculum and its implementation in the classroom, we find a fragmented vision where emotions are excluded and the development of the intellectual capacities of the students is exalted. Thus, it is forgotten that educating from freedom and emotional recognition requires a deep knowledge that is directed towards the formation of a whole being, capable of generating contributions to the society to which he belongs.